2021
DOI: 10.1016/j.bbamcr.2020.118913
|View full text |Cite
|
Sign up to set email alerts
|

NCOA4-mediated ferritinophagy promotes ferroptosis induced by erastin, but not by RSL3 in HeLa cells

Abstract: Ferroptosis is a regulated cell death characterized by a lethal accumulation of lipid peroxides due to an increase of intracellular iron and a decrease of antioxidant capacity. The reduction of antioxidant activity is obtained by using chemical agents, such as erastin and RSL3, the first one inhibiting the transmembrane cystine-glutamate antiporter causing a cysteine and glutathione depletion and the second one inactivating directly the glutathione peroxidase 4 (GPX4) respectively. The role of iron and its rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 59 publications
4
49
0
Order By: Relevance
“…Additionally, knockdown of GCH1 suppressed FTH1 protein levels ( Figure 1H ). Previous studies demonstrated that nuclear receptor coactivator 4 (NCOA4)-mediated selective autophagic turnover of FTH1 (namely ferritinophagy) is necessary for erastin but unnecessary for RSL3 ( Liu et al, 2020 ; Mancias et al, 2014 ; Gryzik et al, 2021 ). To investigate whether GCH1/BH4 deficiency selectively promotes erastin-induced ferroptosis through activation of ferritinophagy, the NCOA4, FTH1, and LC3B protein levels were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, knockdown of GCH1 suppressed FTH1 protein levels ( Figure 1H ). Previous studies demonstrated that nuclear receptor coactivator 4 (NCOA4)-mediated selective autophagic turnover of FTH1 (namely ferritinophagy) is necessary for erastin but unnecessary for RSL3 ( Liu et al, 2020 ; Mancias et al, 2014 ; Gryzik et al, 2021 ). To investigate whether GCH1/BH4 deficiency selectively promotes erastin-induced ferroptosis through activation of ferritinophagy, the NCOA4, FTH1, and LC3B protein levels were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, METTL3 acts as the target of miR-4443, and regulates the expression of FSP1 to mediate the ferroptosis of non-small cell lung cancer ( Song et al, 2021 ). Autophagy may also represent a targeted pathway by which to regulate the sensitivity of cells to ferroptosis ( Gryzik et al, 2021 ). BECN1 is a key protein that regulates autophagy and promotes ferroptosis by regulating the activity of the cysteine/glutamate antiporter (also referred to as system Xc-) ( Kang et al, 2018 ).…”
Section: The Role Of M 6 a In Pcdmentioning
confidence: 99%
“…Nuclear Receptor Coactivator-4 (NCOA4) mediates the degradation of ferritin in an autophagy-dependent pathway where iron is isolated from ferritin and the accumulated free ferrous ions in the cytoplasm promote erastin-induced ferroptosis ( 67 ). Nuclear factor-erythroid 2-related factor 2 (NRF2) regulates the expression of FPN1, FTH, and FTL at the transcriptional level and promotes the stability of the intracellular iron environment ( 68 ).…”
Section: Metabolic Regulation Of Fe 2+mentioning
confidence: 99%